It is not enough to be a member: Conditions for health benefits in associative participation - Lima, M. L.; Camilo, C.; Quintal, F.; Palacin-Lois, M. (Revista de Psicologia Social, 2021)
Involvement in social and community activities has been identified as a key factor in health and well-being. This paper focuses on the health and well-being benefits of a particular type of group involvement: associative participation. The main aim is to identify the type of participation that brings more benefits to the members. Based on previous research, we expect that health and well-being would be higher when there is engagement with the association, when group involvement is more intense and when the type of group involvement is deeper (voluntary work or associative leadership). An 848-individuals sample, recruited from Portugal, Spain and Brazil, responded to an online survey disseminated mainly through associations. Findings show that participation in the associative movement is positively associated with the mental health, physical health and well-being of the associates, but that this effect is only evident for more involved types of participation. Our results suggest that the quality of involvement is associated with a positive outcome: participating in the activities, doing voluntary work or serving as an associative leader.